Respuesta :
Answer: Option B. [tex]16^4[/tex] is the correct answer.
Explanation: Since, Given expression is [tex](1/16)^-4[/tex]
And, we can write [tex](\frac{1}{16})^{-4}= 1^{-4}/16^{-4}=1/16^{-4}[/tex]
since, we know that, [tex]a^m=1/a^-m[/tex]
similarly, we can write, [tex]1/16^{-4}=\frac{1}{1/16^4} =16^4[/tex].( because, we can write, [tex]\frac{a}{b/c} =\frac{ac}{b}[/tex].)
hence [tex](1/16)^-4=16^4[/tex] is correct.
Answer:
[tex]\large\boxed{B)\ 16^4}[/tex]
Step-by-step explanation:
[tex]\text{Use}\ a^{-n}=\left(\dfrac{1}{a}\right)^n\\\\\left(\dfrac{1}{16}\right)^{-4}=\left(\dfrac{16}{1}\right)^4=16^4[/tex]